2018
DOI: 10.3390/nu10091163
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Hungry College Students Not Seeking Help? Predictors of and Barriers to Using an On-Campus Food Pantry

Abstract: Background: The number of food pantries on U.S. college campuses has increased in response to students’ food insecurity, but limited information is available to describe the impact of this resource. The objective of this cross-sectional investigation was to examine the relationship between food insecurity and food pantry awareness, use, and perceived barriers to use. Methods: Students attending the University of Florida in fall 2017 (n = 899) completed the United States Department of Agriculture (USDA) Adult F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
144
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 23 publications
15
144
1
Order By: Relevance
“…Nonetheless, some students discussed experiencing shame and stigma in accessing these services. Food banks are, evidently, unlikely to be a "catch-all" solution for food insecurity [42], as some students yearn to access food in a dignified and socially acceptable manner. Therefore, with adequate financial support, guidance and tools that may improve their access to food, this study suggests that some students value autonomy and capacity to make healthier choices without compromising their dignity.…”
Section: Significance Of Findingsmentioning
confidence: 99%
“…Nonetheless, some students discussed experiencing shame and stigma in accessing these services. Food banks are, evidently, unlikely to be a "catch-all" solution for food insecurity [42], as some students yearn to access food in a dignified and socially acceptable manner. Therefore, with adequate financial support, guidance and tools that may improve their access to food, this study suggests that some students value autonomy and capacity to make healthier choices without compromising their dignity.…”
Section: Significance Of Findingsmentioning
confidence: 99%
“…Shockingly, the findings showed that student food insecurity prevalence was 21%; a rate higher than the national average at the time of 11% [111] and nearly three times higher than the average prevalence in the state of Hawaii (7.8%) [112]. This first study was monumental in establishing that food insecurity might be a challenge many college students face and set forth the precedence for investigation on other including Alabama [27,115], Arizona [25,120], California [109,118,121,122], Florida [123], Hawaii [110], Illinois [124], Maryland [29], Massachusetts [125], Michigan [24],…”
Section: Food Insecurity Among College Students In the United Statesmentioning
confidence: 99%
“…A demographic variable identified as a potential risk factor for college food insecurity, similar to national food insecurity, is race/ethnicity. College students that classify as minority status have been identified in multiple studies to have higher prevalence of food insecurity [24,29,110,115,123,124,129,131,136,143].…”
Section: Information Could Help Eligible College Students Access Fedementioning
confidence: 99%
See 2 more Smart Citations